The Role of Legal Politics in the Formulation of Law No. 1 Year 2023 on the Criminal Code - G, Angga A; Utomo, Budi; Syam, Fauzi (Fakultas Syariah INSURI Ponorogo, 2023)
The Criminal Code is an important legal instrument in building the criminal justice system in Indonesia. In accordance with the times, the government enacted Law No. 1 of 2023 on the Criminal Code (National Criminal Code) as a replacement for the old Criminal Code (Law No. 1 of 1946). In the formation of Law No. 1 of 2023, there is a role of legal politics in order to create regulations that are in accordance with the conditions of the Indonesian nation. This study aims to determine the role of legal politics in the formation of Law No. 1 of 2023. The research method used in this research is normative juridical research method using statutory approach, case approach, comparative approach, conceptual approach. The results of this study show that legal politics plays an important role in the formation of Law No. 1 of 2023, where legal politics plays a role in determining the direction of policies regulated in the National Criminal Code relating to recodification of criminal law, democratization of criminal law, consolidation of criminal law, and adaptation/harmonization to changes in the punishment system.